Tentang Kematian Menurut Kaum Epikurean - Yohanes Theo (Universitas Katolik Parahyangan, 2023)
Epicurus had four remedies called tetrapharmakos, which were as follows: 'Don't fear God, don't worry about death: what is good is easy to get, and what is terrible is easy to endure.' Death should not be feared because when it arrives, we are no longer capable of experiencing it. In reality, why do humans fear death? This issue has been examined using the research method of studying literature, particularly the philosophical thoughts of Epicureans. Many of the implicit fears humans have about death are actually fears of suffering (pain). Those who are excessively afraid of death and plan for it in great detail end up disturbing their inner peace and, as a result, they are not happy. Therefore, Epicureans suggest that we should enjoy the present moment. Death will certainly come, but we can face it with a calm and undisturbed soul (ataraxia), which is the happiness that Epicureans seek to achieve.